Costello Syndrome. A case report - Yadelis Maldonado Martínez; Alexander Torres Molina; Diorgis Duran Lobaina (Medisur)
Costello syndrome is an extremely rare multisystem congenital disorder; only about 250 cases have been described in the literature. Its inheritance pattern is considered to be autosomal dominant, although most cases are sporadic, suggesting de novo dominant mutations. The case of a 7-year-old patient from the Frank País municipality in Holguín with clinical manifestations consistent with Costello syndrome is presented. The clinical study and description of his physical characteristics were performed, detecting as main distinctive features: storage disease-like phenotype, failure to thrive, congenital heart disease, coarse facies, mental retardation and humorous personality. Early diagnosis allows early stimulation and intervention, active screening for tumor lesions, as well as provision of genetic counselling to patients.